A residue of motif III positions the helicase domains of motor subunit HsdR in restriction-modification enzyme EcoR124I - Sinha, Dhiraj; Bialevich, Vitali; Shamayeva, Katsiaryna; Guzanova, Alena; Sisakova, Alexandra; Csefalvay, Eva; Reha, David; Krejci, Lumir; Carey, Jannette; Weiserova, Marie; Ettrich, Rüdiger (Journal of molecular modeling, 2018)
Type I restriction-modification enzymes differ significantly from the type II enzymes commonly used as molecular biology reagents. On hemi-methylated DNAs type I enzymes like the EcoR124I restriction-modification complex act as conventional adenine methylases at their specific target sequences, but unmethylated targets induce them to translocate thousands of base pairs through the stationary enzyme before cleaving distant sites nonspecifically. EcoR124I is a superfamily 2 DEAD-box helicase like eukaryotic double-strand DNA translocase Rad54, with two RecA-like helicase domains and seven characteristic sequence motifs that are implicated in translocation. In Rad54 a so-called extended region adjacent to motif III is involved in ATPase activity. Although the EcoR124I extended region bears sequence and structural similarities with Rad54, it does not influence ATPase or restriction activity as shown in this work, but mutagenesis of the conserved glycine residue of its motif III does alter ATPase and DNA cleavage activity. Through the lens of molecular dynamics, a full model of HsdR of EcoR124I based on available crystal structures allowed interpretation of functional effects of mutants in motif III and its extended region. The results indicate that the conserved glycine residue of motif III has a role in positioning the two helicase domains.
Keywords: Multisubunit enzyme complex; adenosintrifosfát; simulace molekulární dynamiky; mutace; Enzyme Activation; interakční proteinové domény a motivy; Principal components analysis; DNA restriction enzymes; Molecular Dynamics Simulation; Amino Acid Sequence; Deoxyribonucleases, Type I Site-Specific; Protein Subunits; analýza hlavních komponent; Molecular modeling; Multienzyme Complexes; podjednotky proteinů; hydrolýza; Principal Component Analysis; Protein Interaction Domains and Motifs; Molecular mechanics; DNA Helicases; restrikční endonukleasy typu I; konformace proteinů; DNA-helikasy; sekvence aminokyselin; aktivace enzymů; multienzymové komplexy; Adenosine Triphosphate; Protein Conformation; Mutation; Domain interactions; Hydrolysis